Enhancing brand experience and brand authenticity: The role of octomodal mental imagery and social presence. - Min Li; Wonjun Chung (PLoS ONE)
This study investigated the impact of Octomodal Mental Imagery (OMI) on brand experience and authenticity in advocating sustainable development and responding to the lack of brand experience and customers' growing demand for authentic brands. The research employed online questionnaire surveys and data collection via Sojump, resulting in 428 valid responses. The collected data were subjected to quantitative analysis, and the study's hypotheses were tested using structural equation modeling. The results showed that all the sensory attributes of OMI (visual, auditory, tactile, gustatory, olfactory) positively influenced customers' brand experience. All the structural attributes of OMI (autonomy, spatial, kinesthetic) positively influenced customers' brand experience. This study also found that customers' brand experience positively influenced brand authenticity, while social presence positively moderated the relationship. This study provides branding managers and scholars with a new reference point and scientific data support for companies to implement brand strategies and marketing models, which will help brands to maintain sustainable development in a competitive business environment.